Depressive Symptoms and Resilience among Pregnant Adolescents: A Case-Control Study. (18th January 2011) - Salazar-Pousada, Danny; Arroyo, Dalton; Hidalgo, Luis; Pérez-López, Faustino R.; Chedraui, Peter
Abstract : Background . Data regarding depression and resilience among adolescents is still lacking. Objective . To assess depressive symptoms and resilience among pregnant adolescents. Method . Depressive symptoms and resilience were assessed using two validated inventories, the 10-item Center for Epidemiologic Studies Short Depression Scale (CESD-10) and the 14-item Wagnild and Young Resilience Scale (RS), respectively. A case-control approach was used to compare differences between adolescents and adults. Results . A total of 302 pregnant women were enrolled in the study, 151 assigned to each group. Overall, 56.6% of gravids presented total CESD-10 scores 10 or more indicating depressed mood. Despite this, total CESD-10 scores and depressed mood rate did not differ among studied groups. Adolescents did however display lower resilience reflected by lower total RS scores and a higher rate of scores below the calculated median (P < .05 ). Logistic regression analysis could not establish any risk factor for depressed mood among studied subjects; however, having an adolescent partner (OR, 2.0 CI 95% 1.06–4.0, P = .03 ) and a preterm delivery (OR, 3.0 CI 95% 1.43–6.55, P = .004 ) related to a higher risk for lower resilience. Conclusion . In light of the findings of the present study, programs oriented at giving adolescents support before, during, and after pregnancy should be encouraged.